Firewall Implementation as a Computer Network Security Strategy for Data Protection - Fauzan Prasetyo Eka Putra; Mohammat Dafid; Imam Syafi’i (Brilliance: Research of Artificial Intelligence, 2025)
Computer network security plays a crucial role in ensuring the integrity, confidentiality, and availability of data in the modern digital era. One of the primary tools used to safeguard networks from unauthorized access and external threats is the firewall. This paper explores the significance of firewalls in protecting network systems by examining their functions, various types, and capability to regulate data traffic. Firewalls work by enforcing specific rules to limit access, effectively reducing the risk of cyber threats such as malware, hacking attempts, and unauthorized intrusions. The study also involves practical observation of firewall implementation in a real network setup to evaluate their efficiency in mitigating security risks. Findings indicate that properly configured firewalls can considerably strengthen a network’s defense. Nevertheless, relying solely on firewalls is insufficient. They should be supported by additional security technologies and best practices to achieve comprehensive network protection. In conclusion, firewalls are essential elements in upholding the reliability and safety of computer networks.